Green Healthcare: Strategies for Implementing Environmentally Friendly Concepts in Primary Health Care - Lamsir, Seno (Oshada, 2025)
Background: The global demand for sustainable healthcare has increased due to the significant contribution of healthcare facilities to carbon emissions, medical waste, and energy consumption. In response to these challenges, green healthcare has emerged as a paradigm that integrates environmental sustainability with the improvement of clinical services. This approach is particularly relevant for primary healthcare facilities, which function as the first point of patient contact and play a strategic role in shaping sustainable health service delivery. Method: This study employed a descriptive qualitative literature-based approach to examine the concept of green healthcare and to identify strategic pathways for its implementation in primary healthcare services. Relevant scholarly articles and policy-oriented literature were analyzed to capture key dimensions, practices, and enabling factors associated with green healthcare initiatives. Results: The findings indicate that the implementation of green healthcare contributes to enhanced operational efficiency, improved patient psychological comfort, more effective waste management, and higher overall service quality. These outcomes are supported through the integration of patient-centered care, green digitalization, evidence-based facility design, and the development of a sustainability-oriented organizational culture. At the same time, several challenges were identified, including budget constraints, workforce readiness, cultural resistance within organizations, and gaps in digital infrastructure, all of which may limit effective implementation. Conclusion: Green healthcare can be effectively realized only when it is adopted as a systemic transformation rather than a standalone technical initiative. Positioning sustainability as an integral part of organizational identity is essential to ensure the long-term success of green healthcare practices in primary healthcare services.